2016
DOI: 10.3389/fpsyg.2016.00785
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Pinyin and Zhuyin Writing Systems on the Acquisition of Mandarin Word Forms by Native English Speakers

Abstract: The role of written input in second language (L2) phonological and lexical acquisition has received increased attention in recent years. Here we investigated the influence of two factors that may moderate the influence of orthography on L2 word form learning: (i) whether the writing system is shared by the native language and the L2, and (ii) if the writing system is shared, whether the relevant grapheme-phoneme correspondences are also shared. The acquisition of Mandarin via the Pinyin and Zhuyin writing syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 21 publications
5
32
1
Order By: Relevance
“…This shows that effects can take place across scripts, and in the absence of relevant GPCs in the L1 writing system. The few previous studies that investigated orthographic effects on phonology across scripts found little or no orthographic effects (Hayes-Harb & Cheng, 2016;Pytlyk, 2011;Showalter & Hayes-Harb, 2015). However, this absence of effects was probably due to lack of familiarity with the orthography or the phonology of the target language, as such studies investigated naïve learners of a novel language and orthography.…”
Section: Effect Of Number Of Letters On Consonant Durationmentioning
confidence: 96%
“…This shows that effects can take place across scripts, and in the absence of relevant GPCs in the L1 writing system. The few previous studies that investigated orthographic effects on phonology across scripts found little or no orthographic effects (Hayes-Harb & Cheng, 2016;Pytlyk, 2011;Showalter & Hayes-Harb, 2015). However, this absence of effects was probably due to lack of familiarity with the orthography or the phonology of the target language, as such studies investigated naïve learners of a novel language and orthography.…”
Section: Effect Of Number Of Letters On Consonant Durationmentioning
confidence: 96%
“…By contrast, other researchers have reported no beneficial effect of exposure to orthographic input on the acquisition of a novel phonological contrast (Durham, Hayes-Harb, Barrios, & Showalter, 2016;Hayes-Harb & Hacking, 2015;Pytlyk, 2011;Showalter & Hayes-Harb, 2015;Simon, Chambless, & Kickhöfel Alves, 2010) or have demonstrated that orthographic input may interfere with the acquisition of target-like L2 phonological representations, particularly when the written input provides learners with "misleading" information about the phonological forms of new words. Interference effects have been reported when L2 orthographic conventions differ from those of the native language (L1; Bassetti, 2006), when grapheme-phoneme correspondences (i.e., the mapping[s] between grapheme and phoneme) are different in the L1 and L2 (Hayes-Harb & Cheng, 2016;Hayes-Harb et al, 2010;Showalter, 2018), or when the L1 and L2 differ in whether or not familiar graphemes signal a contrast (Escudero et al, 2014). Other factors, including the degree of perceptual difficulty posed by the contrast (Escudero, 2015) and the transparency of the L2 writing system (Mok, Lee, Li, & Xu, 2018), have also been found to modulate written input effects.…”
Section: Orthographic Input In L2 Phonolexical Developmentmentioning
confidence: 99%
“…Building on Mathieu (2016) and Hayes-Harb and Cheng (2016), in the present study we investigate the interaction of grapheme familiarity and congruence during the acquisition of a pseudo-Russian lexicon by naïve English learners. The Russian Cyrillic alphabet provides the opportunity for a more ecologically valid study in that the combination of native English speakers and Russian/ Cyrillic allows for grapheme familiarity and congruence effects to be observed within a single writing system.…”
Section: Introductionmentioning
confidence: 99%